Morphogenesis of serial abdominal outgrowths during development of the viviparous dermapteran, <ce:italic>Arixenia esau</ce:italic> (Insecta, Dermaptera) - Bilinski, Szczepan M. (Ventricular Restraint Improves Outcomes in HF Patients with CRT, 2019)
The embryos and first instar larvae of the epizoic earwig, Arixenia esau, develop sequentially in two different compartments of the female reproductive system, that is ovarian follicles and the lateral oviducts (the uterus). Here we show that the second (intrauterine) phase of development consists of three physiologically disparate stages: early embryos (before dorsal closure, surrounded by an egg envelope), late embryos (after dorsal closure, surrounded by an egg envelope) and the first instar larvae (after “hatching” from an egg envelope). Early and late embryos float in the fluid filling the uterus, whereas the first instar larvae develop attached to the uterus wall. Our analyses revealed also that in Arixenia serial multilobed outgrowths develop on dorso-lateral aspects of all abdominal segments. At the onset of the third developmental stage and after liberation from an egg envelope, these outgrowths (or more precisely their lobes) adhere to the epithelium lining the uterus, forming a series of small contact sites, where the mother and embryo tissues are separated only by a thin, presumably permeable, embryonic cuticle. We suggest that all these contact sites collectively constitute a dispersed placenta-like organ involved in the nourishment of the embryo.